Indoxyl sulfate impairs angiogenesis via chronic aryl hydrocarbon receptor activation - Salyers, Zachary R. (Am J Physiol Cell Physiol, 2021)
Chronic kidney disease (CKD) is associated with a substantial increased risk of cardiovascular disease. There is growing evidence that uremic metabolites, which accumulate in the blood with CKD, have detrimental impacts on endothelial cell health and function. However, the molecular mechanisms by which uremic metabolites negatively impact endothelial cell biology are not fully understood. In this study, activation of the aryl hydrocarbon receptor (AHR) via indoxyl sulfate, a known uremic metabolite, was found to impair endothelial cell tube formation and proliferation but not migratory function. Moreover, aortic ring cultures treated with indoxyl sulfate also exhibited decreased sprouting and high AHR activation. Next, genetic knockdown of the AHR using shRNA was found to rescue endothelial cell tube formation, proliferation, and aortic ring sprouting. Similarly, pharmacological AHR antagonism using resveratrol and CH223191 were also found to rescue angiogenesis in cell and aortic ring cultures. Finally, a constitutively active AHR (CAAHR) vector was generated and used to confirm AHR-specific effects. Expression of the CAAHR recapitulated the impaired tube formation and proliferation in cultured endothelial cells and decreased sprouting in aortic ring cultures. Taken together, these data define the impact of AHR activation on angiogenesis and highlight the potential for therapeutic AHR antagonists, which may improve angiogenesis in the context of CKD and cardiovascular disease.